2011
DOI: 10.1177/0961000611424819
|View full text |Cite
|
Sign up to set email alerts
|

Library and Information Science research areas: A content analysis of articles from the top 10 journals 2007–8

Abstract: Rochester and Vakkari, 2003). However, no earlier study has covered authorship patterns and the main themes appearing in professional LIS literature over the period 2007-8. Literature review Content analysis in LISContent analysis provides insight into the development of a profession as it indicates the subject trends and major issues that occupy the profession within a given period of time (Blessinger and Frasier, 2007). Content analysis of LIS research has been the central topic of various studies. Several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 22 publications
6
38
0
6
Order By: Relevance
“…In summary, the papers in the journal were distributed evenly between the single author's papers (50.0%) and joint or coauthored papers (50.0%). The results of the study align with that of previous studies [14,5] that revealed dominance of single authors' papers in LIS research. The results obtained by Aina and Mooko [15] showed that 79.6% of publications in their study were published by single authors while Mujkerjee [6] found that the highest proportion of articles in his study was led by single authorship (35.59%).…”
Section: Extent Of Research Collaboration In Authorship Patternsupporting
confidence: 90%
See 2 more Smart Citations
“…In summary, the papers in the journal were distributed evenly between the single author's papers (50.0%) and joint or coauthored papers (50.0%). The results of the study align with that of previous studies [14,5] that revealed dominance of single authors' papers in LIS research. The results obtained by Aina and Mooko [15] showed that 79.6% of publications in their study were published by single authors while Mujkerjee [6] found that the highest proportion of articles in his study was led by single authorship (35.59%).…”
Section: Extent Of Research Collaboration In Authorship Patternsupporting
confidence: 90%
“…A number of studies have been conducted on bibliometric analysis of publication patterns of individual journals in library and information science (LIS) around the world [3,4,5,6] and Africa (Nigeria) in particular [7,8,9,10,11,12,13]. Aharony [5] did bibliometric analysis to examine authorship patterns in the top ten journals in Library and Information Science (LIS) including core research areas.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas áreas de la GIyC han sido igualmente visibles en la composición temática de la BCI según otros resultados (ej. : Prebor, 2010;Aharony, 2011;Larivière y otros, 2012).…”
Section: Discussionunclassified
“…Quantitative content analysis is "a research technique for making replicable and valid inferences from texts (or other meaningful matter) to the contexts in their use" (Krippendorf, 2013, p. 24). This method is a standard one in the social sciences, and in the area of information behavior several authors have applied content analysis, including Aharony (2012), Bar-Ilan (2000), Fourie (2012), Julien and Given (2003), Järvelin and Vakkari (1993), Julien (1996), Julien et al (2005), Julien et al (2011), and White and Marsh (2006).…”
Section: Methodsmentioning
confidence: 99%